1997
DOI: 10.1002/eji.1830270513
|View full text |Cite
|
Sign up to set email alerts
|

Insect venom immunotherapy induces interleukin‐10 production and a Th2‐to‐Th1 shift, and changes surface marker expression in venom‐allergic subjects

Abstract: The current study was carried out to elucidate the immunoregulatory changes induced by venom immunotherapy (VIT) in bee or wasp allergic subjects. All subjects included in this study had a history of severe systemic allergic reactions to stings of the respective insect as well as positive skin tests with the respective venom or venom-specific IgE in the sera. Parameters assessed in peripheral blood mononuclear cells (PBMC) before and after initiation of VIT (rush therapy reaching a maintenance dose of 100 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
188
0
9

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(207 citation statements)
references
References 51 publications
10
188
0
9
Order By: Relevance
“…IT has been related to a shift in T cell responses from Th2 to Th1 (15). In our animal model, we confirmed that frequencies of IFN-g-producing CD4 + T cells are increased in lung and draining lymph nodes following IT indicative of a Th1 shift present also in this model (Fig.…”
Section: Allergen Immunotherapy Induces Cd4 + Foxp3 + Treg Cells and supporting
confidence: 85%
See 2 more Smart Citations
“…IT has been related to a shift in T cell responses from Th2 to Th1 (15). In our animal model, we confirmed that frequencies of IFN-g-producing CD4 + T cells are increased in lung and draining lymph nodes following IT indicative of a Th1 shift present also in this model (Fig.…”
Section: Allergen Immunotherapy Induces Cd4 + Foxp3 + Treg Cells and supporting
confidence: 85%
“…IT causes the production of IgG Abs that are supposed to block mast cell degranulation and compete with IgE for the allergen (13). Furthermore, a shift from the pathogenic Th2 to Th1 cells was described that regulates the Th2-mediated inflammation via IFN-g (14,15). Furthermore, regulatory T (Treg) cells have been associated with the effectiveness of IT.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, immunosuppressive IL-Ia can induce specific unresponsiveness (anergy) in peripheral T cells (9,17,(19)(20)(21) and was followed by the IT-induced Thz/Thl switch (22)(23), with a decrease in IL-4 and an increase in IFN-y production in patients undergoing IT. Such changes appear late during the course of SLIT.…”
Section: Discussionmentioning
confidence: 99%
“…Recently the mechanisms operative in SIT have been elucidated. It has been shown that during the administration of increasing doses of allergen, a shift from a typical allergic Th2-response to Th1 could be detected (immunodeviation) and that allergen-specific T cell responses were suppressed (tolerance induction) (17)(18)(19)(20)(21). It was concluded that strategies aiming in the correction of the allergic immune response should target allergenspecific T lymphocytes.…”
mentioning
confidence: 99%